Finite element analysis of new energy vehicle scroll compressor shell under working pressure. (October 2019) - Hu, Shunan; Tang, Mengyi; Ge, Dawei; Guo, Huaming
Abstract: The interference design between the mating surface of shell and retainer in new energy vehicle scroll compressor were important parts of the design of the shell assembly. The finite element analysis of static structure was used to analyze the strength of shell and the deformation value of the mating surface under the working pressure, and minimum surplus were used to analyze whether the matching surface surplus design meet the design requirements. An analytical method was provided for the design of new energy automobile scroll compressor shell by static structure analysis of shell and the interference of mating surface.